(untitled) (Eurasian Journal of History, Geography and Economics, 2022)
This article provides information about the economy of the Jizzakh region, the transition from a centrally planned administrative-command mechanism to a free market economy, a radical reform of the economy of the Jizzakh region in order to form a socially oriented market economy